The Efficacy of Using Team Assisted Individualization (TAI) in Teaching Reading Stories to Indonesian English as Foreign Language (EFL) Students - Soleman Dapa Taka (Institut Agama Islam Negeri Palopo, 2021)
This research aims at finding out the efficacy of using Team Assisted Individualization technique in teaching reading especially stories to Indonesian English as Foreign Language (EFL) students. The main question of this research: Is the use of the Team Assisted Individualization technique effective in teaching reading stories to Indonesian EFL students?. The research can be an addition to the persisting teaching reading stories of English particularly the use of the Team Assisted Individualization technique. This research was conducted at the tenth-grade students at SMA Kristen Mercusuar Kupang, an Indonesian High School. The total number of samples was 25 students. The research used a pre-experimental method with a pre-test and post-test design. The pre-test was given to find out the basic ability of the students in reading stories and the post-test given to find out the students’ improvement in reading stories after giving the treatment by using of Team Assisted Individualization technique. The findings show that using the Team Assisted Individualization technique is effective in teaching reading stories to Indonesian EFL students. It is supported by the result of the significance test through SPSS 20 program that the P was 0.00. Therefore, it is recommended to use the Team Assisted Individualization technique in developing students’ competence in reading stories of Indonesian EFL students.